THE UNITED NATIONS HUMAN RIGHTS COUNCIL’S 2017 REPORT ON FINANCIALIZATION OF HOUSING - Ninepence, Albert Mcbell (Journal of Social Political Sciences, 2022)
Financialization of housing has attracted plenitude of divergent reviews and discussions on the subject matter. The term financialization of housing has been associated with reduced housing affordability in recent debates. Irrespective of financialization of housing cementing a springboard to augment growth of the financial and housing markets, enhanced employments and deepened international trade and relations, it has also created its own setbacks. The financialization of housing has been reviewed to trigger excessive demerits of capital gains exceptions, rent seeking and disregard to upholding and defense of human rights tenets, provisions and conventions. In support of these demerits, the United Nations Human Rights Council’s 2017 report on the financialization of housing underscore financialization of housing creating an overall negative impact. The UN reports posits that the finacialization of housing is now a means to secure and accumulate wealth. Housing is now dehumanized and sold as a commodity on global markets and hence has lost its currency as a universal human right. The copious reviews and contention on the financialization of housing warrants further inquiry into the compendious scholarship. This paper therefore examined and argued in favour of the UN standpoints though making counter perspectives on the discourse of financialization of housing.